Petrology of the Miocene igneous rocks in the Altar region, main Cordillera of San Juan, Argentina: A geodynamic model within the context of the Andean flat-slab segment and metallogenesis - Maydagán, Laura (2011)
The Altar porphyry Cue(AueMo) deposit (31 290 S, 70 280 W) is located in the Andean Main Cordillera of San Juan Province (Argentina), in the southern portion of the flat-slab segment (28e33 S), 25 km north of the world-class porphyry CueMo deposits of Los Pelambres and El Pachón. Igneous rocks in the area have been grouped into the Early Miocene Lower Volcanic Complex -composed of intercalations of lava flows and thin volcaniclastic units that grade upwards to a thick massive tuff- and the Middle-Late Miocene Upper Subvolcanic Suite that consists of a series of porphyritic stocks and dikes and magmatic and hydrothermal breccias. The Lower Volcanic Complex represents an Early Miocene arc (20.8 Ma 0.3 Ma; UePb age) erupted over a steep subduction zone. Their magmas equilibrated with an assemblage consisting of plagioclaseand pyroxene-dominated mineral residues, and experienced fractional crystallization and crustal contamination procesess. Their radiogenic signatures are interpreted to indicate conditions of relatively thickened continental crust in Altar during the Early Miocene, compared to the south and west. The Upper Subvolcanic Suite represents the development of a Middle-Late Miocene arc (11.75 0.24 Ma, 10.35 0.32 Ma; U-Pb ages) emplaced over a shallow subduction zone. A magmatic gap in Altar area betwen the Lower Volcanic Complex and Upper Subvolcanic Suite correlates with documented higher rates of compression in this period, that may have favored the storage of the USS magmas in cameras within the crust. Magmas of the Upper Subvolcanic Suite require a hornblende-bearing residual mineral assemblage that is interpreted to reflect their higher water contents. The relatively uniform radiogenic isotope compositions of the Upper Subvolcanic Suite magmas suggest a homogeneously mixed crust-mantle contribution in the source region. They have similar REE signatures as other fertile intrusives of the flat-slab. The differences observed in their isotopic signatures reflect an increase in the amount of crustal components incorporated into magmas from south (El Teniente) to north (El Indio) which correlate with an increase of crustal thickness. UePb ages of Altar rocks confirm a temporal connection between the ridge arrival and the magmatism associated with mineralization in this zone of the flat-slab segment. We argue that since the Middle-Late Miocene, mantle and lower crust may have been hydratated by fluids from the slab and from the Juan Fernández Ridge at the latitude of Altar, which favored the generation of the Middle-Late Miocene magmas. We also suggest that at this latitude the collision ridge-trench at w11 Ma and the subduction of the Juan Fernández Ridge beneath Altar region at w11e10 Ma may have promoted changes in the tectonic stress regime, allowing the USS magmas to rise to shallower levels in the crust. This may explain the location of a cluster of contemporaneous giant porphyry CueMo deposits including El Pachón-Los Pelambres, the Altar Cu (MoeAu) deposit, and other nearby recently discovered Cu prospects such as Piuquenes, La Coipa, Rincones de Araya and Los Azules.